Application of face centered composite central for optimization of pangasius catfish aquaculture wastewater treatment using potassium ferrate - Phuc , Hoang Gia; Ngan, Dinh Kim; Quan, Dang Ngoc; Khoa , Tran Le Dang; Khoi, Tran Tien; Huy , Nguyen Nhat; Hung, Hoang Phi; Chau, Nguyen Huynh Bao; Thuy, Nguyen Thi (Vietnam Journal of Science and Technology, 2023)
This study applied ferrate in aquaculture wastewater treatment as a multi-purpose agent for pollutants’ oxidation, coagulation, and disinfection. Pangasius catfish aquaculture wastewater samples were collected from three sources and their characteristics were analyzed. Face Centered Composite Central (FCCC) design was utilized for designing the experiments with two independent factors (i.e., pH and ferrate dose) and 6 responses (i.e., effluent concentrations of COD, turbidity, PO43-, TKN, NH4+, and log reduction of coliform). The effects of the two factors on the responses were evaluated and the optimum conditions for each response and also for all responses were discussed. The results showed that the wastewater with low frequencies of water renewing required treatment before discharging or recirculating. pH, ferrate dose, and their interaction affected differently on the responses. The treatment was preferred at the acidic conditions for COD, turbidity, and TKN removals, but the basic environments for coliform, NH4+, and phosphate removals. However, the effect of pH on the treatment depended on the ferrate dose. The optimum working condition for all responses was suggested at pH 3 and 20 mg/L of ferrate dose by which the treatment efficiencies reached 99.985 % (log reduction of 3.826), 96.8 %, 93.0 %, 85.7 %, 61.7 %, and 50.0 %, for coliform, PO43-, turbidity, COD, NH4+, and TKN, respectively. These pollutants’ effluent concentrations met well the allowable values for discharging while the pH value required adjustment post - treatment. A further study focusing on pH and NH4+ treatment is suggested for the recirculation purpose of the treated water.